2021
DOI: 10.1007/s00107-021-01700-7
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study of a yellow birch surface impregnation process

Abstract: Wood is a renewable resource that has been used as a material in appearance products for years. Despite its acceptable mechanical resistance, different modification processes were developed to enhance wood's hardness and make it an even more durable material. Impregnating wood pores with monomers under vacuum-pressure cycle is a common method for that purpose. However, most implemented processes are long and mostly submerge wood into a monomer formulation (Bethell's full-cell process). For that, they can be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The low CR observed in this study can be attributed to lateral impregnation of wood through only one surface (tangential surface and/or radial direction, according to the grain orientation of the exposed surface). The average CR was found to be around 9% for SM across all five formulations, which was expected based on previous studies (Frias et al, 2021;Triquet et al, 2021). The samples were sealed with aluminum tape, which caused air to become trapped in the sample.…”
Section: Chemical Retentionsupporting
confidence: 75%
See 1 more Smart Citation
“…The low CR observed in this study can be attributed to lateral impregnation of wood through only one surface (tangential surface and/or radial direction, according to the grain orientation of the exposed surface). The average CR was found to be around 9% for SM across all five formulations, which was expected based on previous studies (Frias et al, 2021;Triquet et al, 2021). The samples were sealed with aluminum tape, which caused air to become trapped in the sample.…”
Section: Chemical Retentionsupporting
confidence: 75%
“…The formulation viscosity is a parameter impacting the penetration of monomers into the vessels or cell walls. Frias et al showed that low monomer viscosity leads to higher amounts of impregnated monomer (Frias, Blanchet, Bégin-Drolet, Triquet, & Landry, 2021). The viscosities of primary formulations are listed in Table 5.…”
Section: Viscositymentioning
confidence: 99%
“…The anatomical orientation of wood structures significantly influences the wood impregnation process (Frias et al, 2021;Hass et al, 2012;Tondi et al, 2013;Ponomarev et al, 2021bPonomarev et al, , 2022. The obtained images of the distribution of the impregnating composition (Figure 4b and d) show that its movement occurs along the path of least resistance in the end direction along large anatomical structures, such as vessels and fibers.…”
Section: Study Of the Porosity And Distribution Of The Impregnating C...mentioning
confidence: 96%
“…The CA preservative was impregnated into lodgepole pine and scotch pine laminates through a highpressure tank using Bethell's full-cell process (Frias et al 2021). The full-cell process was divided into three stages.…”
Section: Preparation Of Preservative Treated Glulam Laminatementioning
confidence: 99%